Mobile elements and mitochondrial genome expansion in the soil fungus and potato pathogen Rhizoctonia solani AG‐3. Issue 2 (17th February 2014) - Losada, Liliana; Pakala, Suman B.; Fedorova, Natalie D.; Joardar, Vinita; Shabalina, Svetlana A.; Hostetler, Jessica; Pakala, Suchitra M.; Zafar, Nikhat; Thomas, Elizabeth; Rodriguez‐Carres, Marianela; Dean, Ralph; Vilgalys, Rytas; et al.
Abstract The soil fungus Rhizoctonia solani is an economically important pathogen of agricultural and forestry crops. Here, we present the complete sequence and analysis of the mitochondrial genome of R. solani, field isolate Rhs1AP. The genome (235 849 bp) is the largest mitochondrial genome of a filamentous fungus sequenced to date and exhibits a rich accumulation of introns, novel repeat sequences, homing endonuclease genes, and hypothetical genes. Stable secondary structures exhibited by repeat sequences suggest that they comprise functional, possibly catalytic RNA elements. RNA‐Seq expression profiling confirmed that the majority of homing endonuclease genes and hypothetical genes are transcriptionally active. Comparative analysis suggests that the mitochondrial genome of R. solani is an example of a dynamic history of expansion in filamentous fungi.